2012
DOI: 10.1186/1743-8977-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silica nanoparticles size-dependently aggravate atopic dermatitis-like skin lesions following an intradermal injection

Abstract: BackgroundDue to the rising use of nanomaterials (NMs), there is concern that NMs induce undesirable biological effects because of their unique physicochemical properties. Recently, we reported that amorphous silica nanoparticles (nSPs), which are one of the most widely used NMs, can penetrate the skin barrier and induce various biological effects, including an immune-modulating effect. Thus, it should be clarified whether nSPs can be a risk factor for the aggravation of skin immune diseases. Thus, in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 36 publications
(38 reference statements)
3
47
0
1
Order By: Relevance
“…351 Although nanoparticle-induced atopic dermatitis has not been reported, some nanoparticles, including TiO 2 , polystyrene, and amorphous SiO 2 nanoparticles, exacerbate atopic dermatitis by acting as allergens after intradermal injection. [352][353][354] This activity may further enhance the excessive induction of total IgE and cause a stronger systemic Th2 response. 354 Phototoxicity describes an inflammatory skin reaction that results from the topical application of chemical substances and subsequent exposure to light, particularly ultraviolet A radiation (320-400 nm).…”
Section: 350mentioning
confidence: 99%
See 1 more Smart Citation
“…351 Although nanoparticle-induced atopic dermatitis has not been reported, some nanoparticles, including TiO 2 , polystyrene, and amorphous SiO 2 nanoparticles, exacerbate atopic dermatitis by acting as allergens after intradermal injection. [352][353][354] This activity may further enhance the excessive induction of total IgE and cause a stronger systemic Th2 response. 354 Phototoxicity describes an inflammatory skin reaction that results from the topical application of chemical substances and subsequent exposure to light, particularly ultraviolet A radiation (320-400 nm).…”
Section: 350mentioning
confidence: 99%
“…[352][353][354] This activity may further enhance the excessive induction of total IgE and cause a stronger systemic Th2 response. 354 Phototoxicity describes an inflammatory skin reaction that results from the topical application of chemical substances and subsequent exposure to light, particularly ultraviolet A radiation (320-400 nm). 355 Because some nanoparticles are used in cosmetics, their potential phototoxicity is a matter of concern.…”
Section: 350mentioning
confidence: 99%
“…For example, we have reported that amorphous silica nanoparticles (diameter less than 100 nm), unlike the bulk material, can enter the sys-temic circulation through the skin and nasal or oral mucosa and be distributed to several tissues such as liver or brain. [11][12][13] We have also reported that in mice silica nanoparticles with diameter of 70 nm can cross the placental barrier and migrate to the fetal brain and liver, 14) and that systemic administration of the silica nanoparticles impairs blood clotting, induces disseminated intravascular coagulation syndrome, and injures the placenta resulting in intrauterine growth restriction and developmental neurotoxicity in the fetus. 14,15) 2.1.…”
Section: Safety Of Nanoparticlesmentioning
confidence: 95%
“…Almost all NPs that are administrated systematically are coated with electrically neutral hydrophobic surface layers called a "stealth coating" which extends the half-life of NPs to >40 h (Moghimi et al, 2001). Administration of NPs via intradermal or subcutaneous injection showed a different distribution depending on the absence or presence of coatings (Hirai et al, 2012;Liu et al, 2014). The degree of NPs coating plays an important factor in reaching targeted tissues (Liu et al, 2014).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…However, antiangiogenic factors can cause incompatible expansion and defects in the architecture of tumour vasculature (Fukumura and Jain, 2007;Hanahan and Folkman, 1996). Studies using transplanted rodent tumours revealed that the pore size of tumours microvessels range between 100 nm to 780 nm in diameter, therefore; this is an important feature in the extravasation of NPs (Hobbs et al, 1998;Li and Huang, 2010). Additionally, tumours commonly have poor lymphatic drainage, which can reduce the removal of NPs (Maeda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%